DYNAMICS AND CHALLENGES OF VOCATIONAL GUIDANCE FOR STUDENTS WITH DISABILITIES AT INCLUSIVE VOCATIONAL HIGH SCHOOLS IN SURAKARTA - Dzullia, Cahaya Dwi; Sunardi, Sunardi; Yuwono, Joko (International Journal of Cultural and Social Science, 2025)
Effective vocational guidance is crucial for students with disabilities in inclusive settings. This preliminary study describes its implementation at the Inclusive State Vocational High School in Surakarta, focusing on the pre-production, production, and post-production stages. Using a descriptive qualitative approach with observation, in-depth interviews, and documentary studies, this research involved guidance counselors and students with disabilities. Findings show that while the guidance process includes potential identification and transition facilitation, its effectiveness is hampered by significant challenges: limited resources, suboptimal learning adaptation, and insufficient networking with inclusive industries. This study highlights the need to develop a more adaptive and sustainable vocational guidance model for this context.